MIDWIVES' KNOWLEDGE ABOUT RESPECTFUL MATERNITY CARE (RMC) IN CHILDBIRTH SERVICES - Heni Dian Rizqi Mubashiroh; RR. Catur Leny Wulandari; Emi Sutrisminah (Journal of Advanced Nursing and Health Sciences, 2026)
Background: Respectful Maternity Care (RMC) is childbirth care that respects the dignity, rights, privacy, and choices of mothers giving birth. Midwives’ knowledge is important in supporting the implementation of RMC.Methods: This descriptive quantitative study was conducted as a sub-study within a broader research project at the B-31 Obstetrics Unit of Dr. Kariadi General Hospital, Semarang, from December 2025 to August 2026. Data were collected from December 31, 2025, to January 4, 2026. A total of 34 midwives were recruited using total sampling. Knowledge was measured using the 23-item knowledge section of the MKP-RMC and analyzed using univariate analysis.Results: All respondents (100%) demonstrated good knowledge, with scores ranging from 21 to 23, a mean of 22.82 ± 0.46, and a median of 23.00. Five RMC indicators achieved 100% correct responses, while Freedom from Harm and Ill Treatment and Timely and High-Quality Care reached 98.0% and 96.1%, respectively.Conclusion: Midwives demonstrated good knowledge of RMC, although several aspects require further strengthening. The findings are setting-specific and do not indicate actual implementation of RMC. Further research should examine clinical practice and women’s care experiences.